Addressing gender-based impacts of climate change: A case study of Guinayangan, Philippines - Rosimo, Magnolia M.; Gonsalves, Julian Francis; Gammelgaard, Johanna; Vidallo, Rene R.; Monville-Oro, Emilita (2018)
This brief summarizes the findings of a case study of a diversification effort undertaken in Guinayangan Climate-Smart Village. Small livestock systems, a climate-smart agriculture practice, present a less risk-prone livelihood venture. It can feature as a diversification agenda, reducing the risks from crop failure and are relevant to all ecosystems. Small livestock initiatives can benefit women as it provides them with a low-labor and manageable economic option, which requires a small startup investment.